(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Otroshenko A. I. Keywords: comparative analysis, early English translations of the Gospel after St. Luke, different translators, Vulgate abstract. The article is devoted to the comparative analysis of various tense forms in two early English translations of the Gospel after St. Luke and the corresponding Vulgate abstract. It offers an explanation of marked differences in the use of tense forms by different translators. The author underlines the special nature of the given texts conditioned by them being translations of the Scriptures. At the same time the first translators of the Gospel made their own independent choices of language units in the English versions which are different from the corresponding Vulgate abstract.